2019
DOI: 10.1096/fj.201801768rr
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembling peptide modified with QHREDGS as a novel delivery system for mesenchymal stem cell transplantation after myocardial infarction

Abstract: The lower cell survival and retention in the hostile microenvironment after transplantation has been implicated as a major bottleneck in the advancement of stem cell therapy for myocardial infarction (MI). In this study, we designed a novel self‐assembling peptide (SAP) by attaching prosurvival peptide QHREDGS derived from angiopoeitin‐1 to the known SAP, RADA16‐I. The mesenchymal stem cells (MSCs) were harvested from male rats and cytoprotective effect of this designer SAP (DSAP) on cultured MSCs was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…The advantage of this molecular building block, compared with other self‐assembling peptides (Table 2), is its similarity to the RGD (arginine–glycine–aspartic acid residues) tripeptide, a sequence within fibronectin that favors cell attachment or archorage. It has excellent regenerative potential as fillers or scaffolds for a variety of tissue and organ, [ 9b ] especially in human neural growth regeneration, [ 67 ] mesenchymal stem cell transplantation, [ 84 ] and cardiac cell transplantation therapy for fibrotic tissue remodeling. [ 85 ] Compared to intramyocardial MSC injection in rat, more cardiac functionality, greater initial retention and survival of donor mesenchymal stem cells (MSCs) are observed in the epicardium with the instantly‐produced PuraMatrix hydrogel incorporating MSCs (epicardial PM‐MSC therapy), by which a group of tissue repair‐related genes are upregulated.…”
Section: Diverse Self‐assembling Peptide Hydrogels and Their Applicatmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of this molecular building block, compared with other self‐assembling peptides (Table 2), is its similarity to the RGD (arginine–glycine–aspartic acid residues) tripeptide, a sequence within fibronectin that favors cell attachment or archorage. It has excellent regenerative potential as fillers or scaffolds for a variety of tissue and organ, [ 9b ] especially in human neural growth regeneration, [ 67 ] mesenchymal stem cell transplantation, [ 84 ] and cardiac cell transplantation therapy for fibrotic tissue remodeling. [ 85 ] Compared to intramyocardial MSC injection in rat, more cardiac functionality, greater initial retention and survival of donor mesenchymal stem cells (MSCs) are observed in the epicardium with the instantly‐produced PuraMatrix hydrogel incorporating MSCs (epicardial PM‐MSC therapy), by which a group of tissue repair‐related genes are upregulated.…”
Section: Diverse Self‐assembling Peptide Hydrogels and Their Applicatmentioning
confidence: 99%
“…Based on the molecular self‐assembly in PuraMatrix hydrogel, the peptide motif QHREDGS derived from angiopoeitin‐1 is tethered to RADA16‐I peptide. [ 84 ] When carried the MSCs in hydrogel and transplanted into the border of the infarcted cardiac area, the functionalized PuraMatrix hydrogel increases the proliferation of MSCs and decreases apoptosis of MSCs and in situ promote angiogenesis and paracrine by the secretion of IGF‐1 and HGF in rat models. Except of topographic benefits and diverse peptide backbones in RADA16‐I peptide and derivatives, many functional motifs are yet tethered to C‐terminus or N‐terminus of peptide backbone to improve molecular building blocks and accurately mimic the ECM features in vivo.…”
Section: Diverse Self‐assembling Peptide Hydrogels and Their Applicatmentioning
confidence: 99%
“…Increasing evidence has indicated that the EV microRNA (miRNA) content as one of their most likely paracrine mechanism(s) of action. Several miRNAs have been associated with MSC-EV cardioprotective, pro-survival and angiogenic effects, including, for example, miR-21 [187]; miR-125b [188]; miR-320d [189]; miR-95-3p [190]; miR-210 [191]; miR-29 and miR-24 [180]. Additionally, EVs have been shown to biochemically restore ATP and NADH levels and redox state within the injured tissue [192].…”
Section: Contribution Of Exogenous Stem/progenitor Cell-evsmentioning
confidence: 99%
“…After injection of RADA16-II into the infarcted myocardium, the empty space of the hydrogel was cellularized by endothelial, smooth muscle, and cardiac cells within days, which showed the cell recruitment potential of the RADA-based hydrogels for endogenous regeneration of infarcted myocardium [30,55]. In order to improve cardiac function, cardioprotective and angiogenic cues such as IGF1 [56], PDGF [54], VEGF [57], FGF [58], Notch1 [16], and QHREDGS [59] have been integrated with the SAP hydrogels.…”
Section: Discussionmentioning
confidence: 96%